Water Balance, Hormone Homeostasis, and Sugar Signaling Are All Involved in Tomato Resistance to Tomato Yellow Leaf Curl Virus . Issue 4 (2nd July 2014) - Sade, Dagan; Sade, Nir; Shriki, Oz; Lerner, Stephen; Gebremedhin, Alem; Karavani, Asaf; Brotman, Yariv; Osorio, Sonia; Fernie, Alisdair R.; Willmitzer, Lothar; Czosnek, Henryk; Moshelion, Menachem
Abstract : Tonoplast water channels contribute to Tomato yellow leaf curl virus resistance through hormone homeostasis and sugar signaling. Abstract: Vacuolar water movement is largely controlled by membrane channels called tonoplast-intrinsic aquaporins (TIP-AQP s). Some TIP-AQP genes, such as TIP2;2 and TIP1;1, are up-regulated upon exposure to biotic stress. Moreover, TIP1;1 transcript levels are higher in leaves of a tomato ( Solanum lycopersicum ) line resistant to Tomato yellow leaf curl virus (TYLCV ) than in those of a susceptible line with a similar genetic background. Virus-induced silencing of TIP1;1 in the tomato resistant line and the use of an Arabidopsis ( Arabidopsis thaliana ) tip1;1 null mutant showed that resistance to TYLCV is severely compromised in the absence of TIP1:1 . Constitutive expression of tomato TIP2;2 in transgenic TYLCV -susceptible tomato and Arabidopsis plants was correlated with increased TYLCV resistance, increased transpiration, decreased abscisic acid levels, and increased salicylic acid levels at the early stages of infection. We propose that TIP-AQP s affect the induction of leaf abscisic acid, which leads to increased levels of transpiration and gas exchange, as well as better salicylic acid signaling.